Identification of proteins from wild cardoon flowers (Cynara cardunculus L.) by a proteomic approach - Ben Amira, Amal; Bauwens, Julien; De Pauw, Edwin; Besbes, Souhail; Attia, Hamadi; Francis, Frédéric; Blecker, Christophe (Journal of chemical biology, 2017)
Proteomic approach was applied to identify total proteins, particularly the enzymatic content, from wild cardoon flowers. As the selection of an appropriate sample preparation method is the key for getting reliable results, two different extraction/precipitation methods (trichloroacetic acid and phenol/ammonium acetate) were tested on fresh and lyophilized flowers. After two-dimensional electrophoresis (2D–E) separations, a better protein pattern was obtained after phenol extraction from lyophilized flowers. Only 46 % of the total analyzed spots resulted in a protein identification by mass spectrometry MALDI-TOF. Four proteases (cardosins A, E, G, and H), which have become a subject of great interest in dairy technology, were identified. They presented molecular weights and isoelectric points very close and high levels of homology between matched peptides sequences. The absence of the other cardosins (B, C, D, and F) could be an advantage, as it reduces the excessive proteolytic activity that causes bitter flavors and texture defects, during cheese making.